Pelatihan Pemanfaatan Artificial Intelligence Dalam Pembuatan Konten Media Sosial Untuk Publikasi Kegiatan Karang Taruna RT 07 Kelurahan Duri Pulo, Kecamatan Gambir, Jakarta Pusat - Wahyu Pramusinto; Ika Susanti; Bruri Trya Sartana; Ferdiansyah; Sejati Waluyo (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Karang Taruna, as a forum for developing the younger generation, has a strategic role in developing creativity, cohesiveness, and social participation of youth at the RT/RW to sub-district levels. Various social, environmental, youth, and entrepreneurial activities have been carried out regularly; however, the use of social media to document and publicize these activities has not been carried out optimally. In the digital era, the ability to produce interesting and relevant activity content is an important need to increase the visibility of Karang Taruna's activities while encouraging youth involvement. The problem faced is how to determine and manage content in a good and sustainable manner, as well as how to utilize Artificial Intelligence (AI) technology as a tool to help produce social media content. As a solution to this problem, this Community Service activity was designed in the form of training on the use of AI in creating social media content for Karang Taruna activities. Utilizing existing social media, as well as how to manage and create content in a productive and interesting way. Through this training, Karang Taruna members are expected to be able to produce better activity content, increase publication of organizational activities, strengthen internal cohesion, and increase youth participation in every activity carried out.